CEGAH KOMPLIKASI DIABETES MELALUI PEMERIKSAAN KOLESTEROL DALAM DARAH BAGI MASYARAKAT RT 01 DAN RT 07 RW 02 KELURAHAN SUKAJAYA PALEMBANG - Margareta Haiti; Lidwina Septie Ch (Jurnal Abdimas Musi Charitas, 2017)
Diabetes mellitus caused by reduced insulin levels in the blood, then the blood sugar can not be processed into energy consequently blood sugar levels will increase excessively. Excessive sugar will damage the blood vessels, because sugar can not be processed into energy in people with Diabetes Mellitus. Then the energy must be made from other sources such as fat and protein. As a result, cholesterol that forms in the metabolic chain of fat and proteins can accumulate and threaten blood vessels. atherosclerosis will attack almost all blood vessels, especially peripheral vessel tissue, this is the basis of the emergence of various complications of Diabetes Mellitus. Examination of cholesterol levels in blood was conducted at Sukarami Village office on February 11, 2017. Of 40 people examined there were 14 people with cholesterol levels above 200 mg / dl. Obtained 40 people who checked blood cholesterol levels. Keywords: cholesterol, diabetes mellitus